A domino reaction strategy for facile and modular construction of synthetically challenging functionalized ortho-fluoroanilines - Grau, Benedikt; Kohlbauer, Sascha; Gu, Yun Gyeong; Hahn, Friedrich; Lösing, Josephine; Wangen, Christina; Stangier, Maximilian; Ackermann, Lutz; Marschall, Manfred; Tsogoeva, Svetlana (Organic Chemistry Frontiers, 2024)
The selective formation of ortho-fluoroanilines, representing versatile intermediates for the pharmaceutical and fine chemical industries, relies to date on, e.g., transition-metal-catalyzed fluorination of azobenzenes, which must be preformed from aniline derivatives. While few efficient methods for aniline synthesis were reported, sustainable, straightforward, and selective synthesis of fluoroanilines, and in particular ortho-fluoroanilines, remains challenging. Herein, we describe a domino approach that involves the simultaneous construction of a benzene ring and the installation of both amine and fluorine groups in a single operation under metal-free conditions, starting from readily available acyclic compounds. The developed atom- and cost-efficient, highly convenient, selective, and environmentally friendly four-step domino process allows the formation of a variety of functionalized ortho-fluoroanilines with yields of up to 80% and bypasses the selectivity issues of transition-metal-catalyzed aniline fluorination reactions. Furthermore, we show that the new domino products can efficiently be utilized to synthesize fluorinated azo dye and (tetrahydro)quinazoline derivatives in a bioactive form, i.e., possessing a first-time proven micromolar antiviral activity and high selectivity (EC50 (HCMV) down to 1.9 ± 0.7 μM, CC50 up to >100 μM), under conventional and/or visible-light mediated conditions.
CRIS-Team Scopus Importer:2024-10-25